2020
DOI: 10.5539/jas.v12n11p260
|View full text |Cite
|
Sign up to set email alerts
|

Genotype Effect on Proximate and Mineral Analysis of Safflower as a Green Leafy Vegetable

Abstract: Two field trials were carried out at the Botswana University of Agriculture and Natural Resources Content Farm (59o24′S, 95o25′E and 993 m above sea level) in Southern Region of Botswana, to evaluate the effects of genotypes on proximate and mineral composition of safflower leaves. Five safflower genotypes (Kiama composite (local), Sina-PI-537598, Gila-PI-537692, PI-537636 and PI-527710) were evaluated in a randomized complete block design (RCBD) with three replications. During the rosette … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…The winter temperature averages in the current study were below the optimal germination temperatures as reported by Torabi et al (2015). A similar genotypic variation in response to a number of days to emergence has been reported (Moatshe & Emongor, 2019).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The winter temperature averages in the current study were below the optimal germination temperatures as reported by Torabi et al (2015). A similar genotypic variation in response to a number of days to emergence has been reported (Moatshe & Emongor, 2019).…”
Section: Discussionsupporting
confidence: 76%
“…affected by the planting season with winter sowing being the most favourable and summer planting being the least favourable (Emongor et al, 2017;Moatshe & Emongor, 2019). Other studies have reported that safflower does better when sown in autumn than in winter (Golzarfar et al, 2012;Sampaio et al, 2018).…”
Section: Growth Development and Yield Of Safflower Genotypes In Respo...mentioning
confidence: 99%